PHENOMENOLOGICAL STUDY OF THE ALLIANCE OF INDEPENDENT JOURNALISTS (AJI) IN IMPLEMENTING JOURNALIST IDEALISM IN PALEMBANG - Deby Ariyanto; Desy Misnawati; Isnawijayani Isnawijayani (Sean Institute, 2023)
This research aims to explore the phenomenon of the Independent Journalists Alliance (AJI) in implementing journalistic idealism in the city of Palembang. The method employed is phenomenological study, enabling an in-depth understanding of AJI members' experiences, perspectives, and motivations regarding journalistic idealism. Data were collected through in-depth interviews with AJI members and analyzed using a qualitative approach. The research findings reveal the perceptions, challenges, and meanings attributed by AJI members to journalistic idealism within the Palembang context. These findings offer insights into how AJI translates and integrates the values of journalistic idealism into their journalistic practices in the region. The research contributes to a deeper understanding of AJI's role and journalistic idealism within the local and national contexts, as well as its implications for press freedom and journalistic professional integrity.